ANALISIS KELAYAKAN BUKU TEKS BAHASA INDONESIA MAHIR BERBAHASA INDONESIA (MARBI) KELAS VII EDISI REVISI - Nur Alviya, Siti Risna; Mulyaningsih, Indrya; Khuzaemah, Emah (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to determine the feasibility of the revised edition of the revised edition of the Indonesian Advanced Bahasa Indonesia (MARBI) textbook. The assessment of the feasibility of a textbook is based on BSNP standards by analyzing four feasibility including content feasibility, linguistic feasibility, presentation feasibility, and graphic feasibility. This research is included in descriptive qualitative research. The data source of this research is the opinion of the Indonesian language teacher who has used the textbook and the revised edition of the MARBI textbook for grade VII. The data in this study are textual units and non-textual units. Data collection techniques with document analysis, interviews, and fry charts. The data collection instruments used were assessment sheets based on the BSNP, interview guidelines, and fry charts. The validity of the data in this study was obtained from the triangulation of data sources, triangulation of theories, and triangulation of data collection methods. Data analysis was performed interactively with data reduction procedures, data presentation, and drawing conclusions / verification. The results of the feasibility analysis of the MARBI textbook were the content / material feasibility with a value of 76.62%; 2) linguistic feasibility with a value of 82.85%; 3) the feasibility of serving with a value of 83.33%; and 4) the feasibility of the graphics with a value of 82.61%. This feasibility still needs guidance from educators.